2015
DOI: 10.2147/rrtm.s63522
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the spread of plague in Africa

Abstract: Plague is a zoonotic disease which has been responsible for a number of high-mortality epidemics throughout the recorded human history. This review was carried out with the aim of evaluating the current situation of human plague in Africa. The disease was reported from at least 28 countries in the continent, among them eight countries are currently with active human foci. The Democratic Republic of the Congo and Madagascar are the countries with the highest endemicity in the world. A unique gathering of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…However, it is known that after long periods of epidemiological silence, there is the possibility of reemergence (Stenseth et al 2008). As recently reported in foci in Africa (Malek et al 2014), the region is currently responsible for over 90% of the cases registered every year (Raoult et al 2013), and where several countries do not register any recent activity and are strong candidates for reemergence (Lotfy 2015).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, it is known that after long periods of epidemiological silence, there is the possibility of reemergence (Stenseth et al 2008). As recently reported in foci in Africa (Malek et al 2014), the region is currently responsible for over 90% of the cases registered every year (Raoult et al 2013), and where several countries do not register any recent activity and are strong candidates for reemergence (Lotfy 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Although Plague has experienced a decrease in activity during the last century, it is still a present threat. Areas such as sub-Saharan Africa have been detecting activity in foci that were quiescent for decades (Malek et al 2014, Lotfy 2015). The new cases detected in foci considered dormant for over 30 years has caused the WHO to classify Plague as a re-emerging disease (Richgels et al 2016) and Brazilian foci are likely to resume activity as well (Zeppelini et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the new outbreaks in Madagascar confirm that human plague can be considered an infectious disease reemerging in XXI Century. On the other hand, in a study concerning perspectives on the spread of the plague in Africa it was concluded that all African countries should be concerned by the possible emergence and reemergence of the disease and that it is crucial to implement some preventive measures in these countries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historical documentation of plague in Africa dates back to the early 1900s [20], though it likely occurred well before then. These outbreaks have ranged in size from dozens to thousands of cases [21]. A 2017 outbreak in Madagascar ultimately affected over 2,000 persons, with 202 deaths (case-fatality rate = 8.6%) [19]; this outbreak spread quickly in part due to a weak surveillance system [23].…”
Section: Funding and Disclaimermentioning
confidence: 99%